Butorphanol Promotes Macrophage Phenotypic Transition to Inhibit Inflammatory Lung Injury via κ Receptors - Luan, Guangxin; Pan, Fan; Bu, Lina; Wu, Kaixuan; Wang, Aizhong; Xu, Xiaotao (Frontiers in Immunology, 2021)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is characterized by diffuse inflammation of the lung parenchyma and refractory hypoxemia. Butorphanol is commonly used clinically for perioperative pain relief, but whether butorphanol can regulate LPS-induced alveolar macrophage polarization is unclear. In this study, we observed that butorphanol markedly attenuated sepsis-induced lung tissue injury and mortality in mice. Moreover, butorphanol also decreased the expression of M1 phenotype markers (TNF-α, IL-6, IL-1β and iNOS) and enhanced the expression of M2 marker (CD206) in alveolar macrophages in the bronchoalveolar lavage fluid (BALF) of LPS-stimulated mice. Butorphanol administration reduced LPS-induced numbers of proinflammatory (M1) macrophages and increased numbers of anti-inflammatory (M2) macrophages in the lungs of mice. Furthermore, we found that butorphanol-mediated suppression of the LPS-induced increases in M1 phenotype marker expression (TNF-α, IL-6, IL-1β and iNOS) in bone marrow-derived macrophages (BMDMs), and this effect was reversed by κ-opioid receptor (KOR) antagonists. Moreover, butorphanol inhibited the interaction of TLR4 with MyD88 and further suppressed NF-κB and MAPKs activation. In addition, butorphanol prevented the Toll/IL-1 receptor domain-containing adaptor inducing IFN-β (TRIF)-mediated IFN signaling pathway. These effects were ameliorated by KOR antagonists. Thus, butorphanol may promote macrophage polarization from a proinflammatory to an anti-inflammatory phenotype secondary to the inhibition of NF-κB, MAPKs, and the TRIF-mediated IFN signaling pathway through κ receptors.